Substrate Specificity and Inhibitor Sensitivity of Plant UDP-Sugar Producing Pyrophosphorylases - Decker, Daniel; Kleczkowski, Leszek A. (Frontiers in Plant Science, 2017)
UDP-sugars are essential precursors for glycosylation reactions producing cell wall polysaccharides, sucrose, glycoproteins, glycolipids, etc. Primary mechanisms of UDP sugar formation involve the action of at least three distinct pyrophosphorylases using UTP and sugar-1-P as substrates. Here, substrate specificities of barley and Arabidopsis (two isozymes) UDP-glucose pyrophosphorylases (UGPase), Arabidopsis UDP-sugar pyrophosphorylase (USPase) and Arabidopsis UDP-N-acetyl glucosamine pyrophosphorylase2 (UAGPase2) were investigated using a range of sugar-1-phosphates and nucleoside-triphosphates as substrates. Whereas all the enzymes preferentially used UTP as nucleotide donor, they differed in their specificity for sugar-1-P. UGPases had high activity with D-Glc-1-P, but could also react with Fru-1-P and Fru-2-P (Km values over 10 mM). Contrary to an earlier report, their activity with Gal-1-P was extremely low. USPase reacted with a range of sugar-1-phosphates, including D-Glc-1-P, D-Gal-1-P, D-GalA-1-P (Km of 1.3 mM), β-L-Ara-1-P and α-D-Fuc-1-P (Km of 3.4 mM), but not β-L-Fuc-1-P. In contrast, UAGPase2 reacted only with D-GlcNAc-1-P, D-GalNAc-1-P (Km of 1 mM) and, to some extent, D-Glc-1-P (Km of 3.2 mM). Generally, different conformations/substituents at C2, C4 and C5 of the pyranose ring of a sugar were crucial determinants of substrate specificity of a given pyrophosphorylase. Homology models of UDP-sugar binding to UGPase, USPase and UAGPase2 revealed more common amino acids for UDP binding than for sugar binding, reflecting differences in substrate specificity of these proteins. UAGPase2 was inhibited by a salicylate derivative that was earlier shown to affect UGPase and USPase activities, consistent with a common structural architecture of the three pyrophosphorylases. The results are discussed with respect to the role of the pyrophosphorylases in sugar activation for glycosylated end-products.